Public Service and Public Happiness: Inferences From Big Weibo Datasets for 31 Chinese Provincial Governments - Ding, Yi Zhou (Frontiers in Big Data, 2022)
The change of public service has usually been considered to affect public happiness. However, since publication of the Easterlin Paradox, the causal relationship between public service and public happiness has been furiously questioned by public affairs researchers. It has been documented through resolving the four causal factors of public happiness within public administration, new public administration, new public management, and governance that public-service-driven public happiness may be attributed to four happiness dimensions: Objective Reality, Subjective Reality, Inter-Subjective Reality, And Virtual Reality. This paper reports the results of significance tests of the relationship between public service and public happiness from analyses of large datasets collected from Weibo systems in 31 Chinese provincial governments from 2010 to 2020. The analyses show that the public service change during this period have not yet led to satisfactory improvement in all four happiness dimensions. Finally, we propose strategies for governments to modify public services to enhance public happiness.